تأثير طريقة Make a Match في تعليم المفردات لطلاب الفصل السابع بالمدرسة الحكومية المتوسطة 1 سوجيو لامونجان - Al Muthoharoh, Zulfa; Umi Machmudah; Ma’rifatul Munjiah; Mhd Ibnu Hanan Al Faruqi (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2025)
Abstract This study aims to examine the effect of the Make a Match method on Arabic vocabulary (mufrodat) learning among seventh-grade students at SMP Negeri 1 Sugio Lamongan. Field observations revealed several factors contributing to students’ low comprehension and engagement during the learning process. One key issue is the lack of student practice in mufrodat, such as memorization or interactive activities, as the teaching methods predominantly used by teachers rely on the traditional qirā’ah wa tarjamah (reading and translation) approach. This limited practice has led to suboptimal vocabulary acquisition. Therefore, there is a need for a more effective instructional method to enhance students’ mastery of mufrodat. This research adopts a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. Data were collected through observation, interviews, and vocabulary mastery tests. The results show that the experimental group achieved a higher post-test average score (91.72) compared to the control group (74.03). An independent sample t-test yielded a significance value of 0.00 (p < 0.05), indicating a statistically significant difference between the groups. Thus, the Make a Match method significantly improves vocabulary learning compared to traditional teaching methods. Keywords: Make a Match method; Arabic vocabulary; Arabic learning.